Attitude of Post Graduate Students towards Mobile Learning - Fouzdar, Kusum; Behera, Santosh Kumar (EDUCARE, 2017)
ABSTRACT: There are various ways to use mobile phones for enhancing learning. Mobile phones plays an important role in our day today lives in various purposes. One of the important purposes is learning. Mobile learning, as a novel educational approach, encourages flexibility; students do not need to be a specific age, gender, or member of a specific group or geography, to participate in learning opportunities. Restrictions of time, space, and place have been lifted. Mobile learning is an emerging concept as the development of an adoption rate of mobile technologies increase rapidly on a global scale. While there are as many people using mobile technologies as there are opinions on how mobile technologies will impact e-learning, the majority agrees that mobile learning will play a major role in e-learning. In the present study, the investigators made an attempt to study the attitude of PG (Post Graduate) students of Sidho-Kanho-Birsha University in Purulia District of West Bengal, India. The descriptive survey method was used. One hundred and fifty students (both male and female) reading in Semesters-2nd and 4th were taken as representative sample of the whole population. An attitude scale was used for collecting the data. The means of both groups were tested for significance of difference by using CR (Constructed-Response) test. Results indicated that the attitudes of PG male and female, rural and urban, General and SC/ST (Scheduled Castes/Scheduled Tribes), Semester-2nd and 4th students were statistically not significant. The attitude of PG Arts and Science students was statistically significant and the attitude of PG students towards mobile learning was neither more favourable nor unfavourable, but satisfactory or average.KEY WORDS: Attitude; Mobile Learning; Post Graduate Student; Satisfactory; Enhancing Learning.Â Â About the Authors: Kusum Fouzdar is M.A. Student at the Department of Education, Sidho-Kanho-Birsha University, Purulia, West Bengal 723104, India. Dr. Santosh Kumar Behera is an Assistant Professor at the Department of Education, Sidho-Kanho-Birsha University, Purulia, West Bengal 723104, India. Email address: santoshbehera.jkc@gmail.com How to cite this article? Fouzdar, Kusum & Santosh Kumar Behera. (2017). âAttitude of Post Graduate Students towards Mobile Learningâ in EDUCARE: International Journal for Educational Studies, Vol.9(2), February, pp.111-120. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (January 8, 2017); Revised (January 20, 2017); and Published (February 27, 2017).